Step 1
Name the equations
-2x + 4y = 2 ............................................ 1
-2x + 3y = 1 ............................................. 2
Step 2
Use the Elimination method to find x and y
Step 3
Eliminate x, subtract if the variable has the same sign, and add if the variable has a different sign.
In this case, variable x has the same sign (-).
-2x + 4y = 2
-2x + 3y = 1
0 + y = 1
y = 1
Substitute y in equation 1 and find the value of x.
-2x + 4y = 2
-2x + 4(1) = 2
-2x + 4 = 2
-2x = 2 - 4
-2x = -2
x = -2/-2
x = 1
y = 1 and x = 1